Pengaruh Employee Engagement terhadap Kepuasan Kerja dan Turnover Intention Perawat (Studi pada Rumah Sakit Wava Husada Kepanjen Malang) - Rachman, Lutfi; Dewanto, Aryo (Universitas Brawijaya, Indonesia, 2016)
Abstract: Human resources is essential to prevent turnover intention of hospital nurses. Nurses engagement is expected to produce nurses satisfaction and finally lower turnover intention. This study aims to examine the effect of employee engagement on job satisfaction and turnover intention of nurses at Wava Husada Hospital Kepanjen-Malang. The research was a cross sectional research. Sample of the study were 102 nurses who work at inpatient and outpatient unit of Wava Husada Hospital. Questionnaire with 5 point Likert scale was used to measure employee engagement, job satisfaction, turnover intention. Path analysis was used to test the direct and indirect direct effect of the variables. The results showed that employee engagement has direct effect on job satisfaction and turnover intention. On the other hand, job satisfaction has direct effect on turnover intention of nurses in hospitals Wava Husada Kepanjen. The results also indicate that there was an indirect effect of employee engagement on turnover intention through job satisfaction